Nurse AMHPs: an exploratory study of their experiences. Issue 2 (11th December 2018) - Stone, Kevin
Abstract : Purpose: Mental health and learning disability nurses have been eligible to become approved mental health professionals (AMHPs) since 2008, when the Mental Health Act 2007 was implemented. Despite this, there have been proportionally low numbers of these nurses pursuing the AMHP role. The purpose of this paper is to explore the experiences of these nurse AMHPs of training and practice. Design/methodology/approach: Ten practicing nurse AMHPs were recruited from across four local authority sites. Using semi-structured interviews, participants were asked to discuss their experiences of being an AMHP. Findings: The participants highlighted the need to navigate personal, cultural and structural factors relating to accessing and applying for the training, difficulties with agreeing contracts terms, gaining comparative pay and undertaking the role. Research limitations/implications: The limitations of this study are the small number of participants and therefore the generalisability of the findings. Also, respondents were practising AMHPs rather than nurses who considered the role but then rejected it as a career option. Practical implications: This study has led to gain a greater understanding of the experiences of nurse AMHPs. Social implications: The results from this study will assist employing local authorities, and NHS consider the barriers to mental health and learning disability nurses becoming AMHPs. Originality/value: The value of this study is in the insight that provides the experiences of nurse AMHP from applying to training through to being a practising AMHP.